2022
DOI: 10.1177/03400352211066939
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents and consequences of organizational learning in the library: A systematic literature review

Abstract: The aim of this study is to determine the developments and factors that affect organizational learning in libraries. The study uses a systematic literature review method by analysing 20 research articles. The results of the study indicate that there are antecedents and consequences of organizational learning in the library. The research offers a comprehensive framework of the antecedents and consequences of organizational learning in libraries. Library managers can use these results to improve organizational l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Despite claims that mastery- and performance-oriented motivation norms in the workplace can influence organizational learning (Chadwick and Raver, 2015), little has been written about this connection. Few works have explored only intrinsic motivation (see, for example, the systematic review by Srirahayu et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite claims that mastery- and performance-oriented motivation norms in the workplace can influence organizational learning (Chadwick and Raver, 2015), little has been written about this connection. Few works have explored only intrinsic motivation (see, for example, the systematic review by Srirahayu et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The empirical literature on employees' motivation as a predictor of organizational learning capacity is scarce. A systematic review of research on organizational learning within libraries indicated that out of the twenty studies analyzed, only one study focused on the aspect of motivation, specifically delving into the realm of intrinsic motivation (Srirahayu et al, 2022). In their conceptual work, Chadwick and Raver (2015) argued that mastery and performance-oriented norms related to motivation in the workplace can influence information interpretation and integration in general and organizational learning in particular.…”
Section: Teachers' Motivation and Organizational Learning Capacitymentioning
confidence: 99%
“…The study also cites the implementation of online networks, e-commerce platforms, and marketplaces as examples of KM supported by a KMS perspective. Srirahayu, Eliyana, and Anugrah (2022) proffer that KM attempts to create and use space for human interaction, which allows for the formation of intangible assets to help the organization achieve its aims. Findings point out that organisational KM relates to the administration of OK.…”
Section: Understanding Of Knowledge Managementmentioning
confidence: 99%